Avaliação do desempenho de equipas de futebol profissional: Análise das interações entre jogadores - Santos, Francisco José Marques dos (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Information Systems and Technologies Management